CONFLICTS IN PROJECT MANAGEMENT OF BUSINESS STRUCTURES - MELNYCHENKO, Oleksandr; MELNYCHENKO, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Based on the results of the analysis, it was concluded that the successful implementation of any project and meeting the needs of its stakeholders depends on the professional and competent abilities, skills and abilities of the team, as well as the leadership qualities of the project manager and his ability to avoid or prevent the impact of conflicts. The expediency of implementing the conflict management component into the methodical support of project management of the business structure has been proven, which consists of: planning of business project conflict management, conflict identification, conflict analysis, conflict response planning, conflict response implementation, and conflict monitoring. The final list will depend on the type of business structure, the direction of activity and the scale of the project. The purpose of such actions is to obtain a conscious and controlled level of risk in relation to the implementation of the project and the creation of value for the team (social and economic results). Conflicts within a business project can often arise at two levels: 1) individual (conflicts that affect the achievement of individual project goals); 2) general management (conflicts that arise from a combination of individual conflicts, accumulated problems, stresses, force majeure, etc., and which will affect the implementation of the entire project). The project manager should be clearly aware of the consequences that destructive conflicts can lead to and how to improve the impact of constructive conflicts on the results of the project. It was concluded that conflicts can arise during the entire life cycle of an entrepreneurial project, therefore, the project conflict management process should be permanent, from the birth of a business idea to its successful completion and satisfaction of the goals of stakeholders planned in the project. The nature of the occurrence of conflicts in the field of project management of business structures has been investigated. It was found that the formation of a quality project management mechanism of business structures should be based on quality monitoring of conflict situations both in the external and internal environment. The situation becomes more complicated for the manager when implementing projects within the framework of a global or multinational strategy, when one should take into account the peculiarities of the mentality of the target audience, the probability of a conflict of interests of stakeholders and differences in the legal field of business implementation.In this regard, issues of implementation of the main provisions of Ukrainian legislation on these issues into the European legal space, as well as the corporate culture of the business structure itself, are of scientific interest.
Keywords: conflict situation; project management; business structure; project effectiveness; stakeholders; personnel